Stigmatisasi Pemberitaan Terorisme di Media Massa - Mubarok, Mubarok (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2012)
AbstractThe process of stigmatization in mass media encompasses the organization of news production. The journalistic routines of hunting, editing,and writing facts underlies the process of stigmatization. Researcher applies critical discourse analysis using three models of analysis—text, social cognition, and social context—from Teun van Dijk. Researcher puts analysis on news about terrorism taken from Kompas, July-October 2009. Kompas news discourse on terrorism, characteristics of terrorist, and description of the terrorist’s relatives is a reflection that comes from the facts and a representation of the given reality. Mass media plays a role as an arena that represents social facts relying on its newsmaking construction. In representing those social facts, mass media does not work autonomously. It depends on the economical, political, and social interests and publisher intervention. It is about how to select sources, facts, and facts presentation manifested in text to put emphasis on assumption that framework in news production integrates with its vested interests. Keywords: stigmatization, mass media, terrorism, critical discourse analysis